2023
DOI: 10.3390/electronics12163423
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Enhanced Multi-Modal Sensing Platform for Robust Human Object Detection and Tracking in Challenging Environments

Abstract: In modern security situations, tracking multiple human objects in real-time within challenging urban environments is a critical capability for enhancing situational awareness, minimizing response time, and increasing overall operational effectiveness. Tracking multiple entities enables informed decision-making, risk mitigation, and the safeguarding of civil-military operations to ensure safety and mission success. This paper presents a multi-modal electro-optical/infrared (EO/IR) and radio frequency (RF) fused… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, TIR is sensitive to temperature changes, making it useful for detecting thermal variations in objects. In fact, studies have shown that infrared thermal cameras are better at identifying car and bicycle objects compared to visual light cameras, particularly in nighttime operations [2]. This highlights the importance of using infrared thermal data for object detection, as it provides superior performance compared to visual light cameras in identifying objects at night.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TIR is sensitive to temperature changes, making it useful for detecting thermal variations in objects. In fact, studies have shown that infrared thermal cameras are better at identifying car and bicycle objects compared to visual light cameras, particularly in nighttime operations [2]. This highlights the importance of using infrared thermal data for object detection, as it provides superior performance compared to visual light cameras in identifying objects at night.…”
Section: Introductionmentioning
confidence: 99%